Impact of Excessive Use of Mobile Phone on Academic Performance of Students of Mohtarma Benazir Bhutto Shaheed Medical College - Ali, Youmnah; Mushtaq, Sobia; Shahnawaz, Ammara; Un Nisa, Zaib; Irraj Khan, Hafsa; Shahreen, . (Biological and Clinical Sciences Research Journal, 2025)
Mobile phone usage has become deeply embedded in student life, offering both educational utility and considerable distraction. Among medical students, excessive screen time may impair concentration, study habits, and health, ultimately affecting academic outcomes. Objectives: To assess the impact of excessive mobile phone usage on the study patterns and academic performance of medical students and to compare academic outcomes between frequent mobile phone users and those who use mobile phones only when necessary. Methods: A cross-sectional study was conducted from April 2018 September 2018 within the premises of Mohtarma Benazir Bhutto Shaheed Medical College, Mirpur, AJK. A structured questionnaire was administered to students residing in both the college and hostel. Variables included mobile phone usage frequency, study disruptions, social media activity, and self-reported health complaints. Descriptive statistics were used to summarize data, and comparative analysis was applied between high and low phone usage groups. Results: Of the respondents, 46% reported experiencing attention deficits while studying. WhatsApp was the most frequently cited distraction, with 96% of students admitting to using it during study time, followed by Facebook/Instagram (39%). Furthermore, 71% reported using mobile phones for more than two hours during study periods. Health effects included hearing and vision-related issues in 60% of the students. High-frequency users demonstrated poorer academic concentration and greater interference in study routines compared to low-frequency users. Conclusion: Excessive mobile phone usage has a significant negative impact on the academic behavior and health of medical students. It contributes to reduced concentration, study time mismanagement, and increased risk of sensory complaints. To support academic success and student well-being, institutional awareness programs promoting responsible digital habits should be implemented.